IMPLEMENTING ZOOM AS BLENDED LEARNING PLATFORM TO OBTAIN LEARNING PROCESS FROM HOME DURING THE PANDEMIC OF COVID-19 AT MTSN 3 ENREKANG - Indrawati Natsir; Ammang Latifa; Salasiah Ammade (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
The objective of this research was to analyze the students’ perception on using Zoom as blanded learning platform from home during the pandemic of Covid-19.This research used descriptive qualitative. Creswell (2013) noted that descriptive qualitative was about understanding and perspective. The subject of this research were 22 learners (IXa) of MTsN 3 Enrekang. This research applied two kinds of instruments were observation and interview guidance.It found that setting up, getting going, managing activity, winding down, and assessing the students was applied in teaching and learning English. Furthermore, the students’ perception were 1) the zoom application made easire, fun, help the learners in learning English. It proved that there were 17 learners of 22 learners gave positive response about zoom appliacation, 2) the zoom application influenced the learning process in school. It proved that there were 22 learners agreed it, 3) the zoom application influenced enough the English skill of learners. It proved that all learners said yes, and 4) the zoom application made easy to use in learning English. It proved that that 19 learners agreed it.